2013
DOI: 10.1080/15298868.2012.705959
|View full text |Cite
|
Sign up to set email alerts
|

Rejection of Self or Others? Majority–Minority Status Moderates Responses to Strongly Identified Members of the Out-group

Abstract: The actor-partner interdependence model was used to examine how one’s own ethnic identification – and one’s interaction partners’ ethnic identification – predicted reactions to mixed-group discussions. The 104 participants interacted in groups of four, with half from the ethnic majority (European Americans) and half from an ethnic minority (African-, Asian-, or Latino Americans) in each group. Analyses revealed that ethnic identification had generally positive relationships with one’s own outcomes, including g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
1
5
1
Order By: Relevance
“…Therefore, they might have been better acclimated to the experience of intergroup contact and less affected by it. However, while former researchers suggested that prior intergroup connection with the outgroup can be related to reduced levels of anxiety (Christensen & Kerper, 2013; Pettigrew & Tropp, 2006), the current study revealed intermediate levels of anxiety about intergroup contact, with no differences between Jewish and Negev-Arab participants. Moreover, there was also no difference in level of anxiety about intergroup contact at the beginning and end of the school year among both research groups.…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…Therefore, they might have been better acclimated to the experience of intergroup contact and less affected by it. However, while former researchers suggested that prior intergroup connection with the outgroup can be related to reduced levels of anxiety (Christensen & Kerper, 2013; Pettigrew & Tropp, 2006), the current study revealed intermediate levels of anxiety about intergroup contact, with no differences between Jewish and Negev-Arab participants. Moreover, there was also no difference in level of anxiety about intergroup contact at the beginning and end of the school year among both research groups.…”
Section: Discussioncontrasting
confidence: 91%
“…However, several researchers have argued that minority and majority group members struggle with different kinds of threats during intergroup contact. While members of majority groups often worry that they will be perceived as prejudiced and seek to be liked and affirmed as moral by members of the minority group, members of minority groups are motivated to satisfy needs for respect and empowerment (Bergsieker, Shelton, & Richeson, 2010; Christensen & Kerper, 2013; Nadler & Shnabel, 2015; Saguy & Dovidio, 2013). Pettigrew and Tropp’s (2006) meta-analysis of contact effects for majority versus minority group status found that the impact of contact was reliably weaker for members of minority groups.…”
Section: The Research Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Research using the APIM on other types of small groups reveals similar interrelated processes. For example, Christensen and Kerper (2013) noted that several types of self-perceptions, including self-esteem and attraction, were related to partners’ identification with the group. Watson, BarNir, and Pavur (2010) showed that members’ perceptions of student study groups are based on how well one’s partners did on various assignments related to the study group.…”
Section: Modeling Partner Effects In Group Researchmentioning
confidence: 99%
“…Some studies alluding to Blalock's (1967) social context perspective have explored whether the relative size of out-groups in a specific region is a significant predictor of perceptions of threat and competition among the members of different groups. Early and recent studies testing this theory consistently found that larger populations of minority groups are associated with greater white racial animosity and/or prejudicial attitudes (Bobo 1988; Christensen and Kerper 2013; Frisbie and Niedert 1977; Glaser 1994; Key and Heard 1949; Taylor 1998; Wong 2007; Wong et al 2012; Wright 1977).…”
Section: Social Context and Racial Relationsmentioning
confidence: 99%